Slope Stability Analysis Under Rapid Drawdown Conditions At Susu Dam With Finite Element Method Using Rs2 - Douglas, Bong Lip Seng (Universiti Sains Malaysia, 2017)
This research focused on the natural slopes stability analysis at Susu Dam with Finite Element Method (FEM) computer program RS2. Slope stability is important in the design and construction of earth dam because exposed to dangerous conditions such as rapid drawdown which is one of the main critical factor that contributes to slope failure. The rapid drawdown condition arises when submerged slopes experience rapid reduction of the external water level. The slope stability analysis using RS2 to calculate the factor of safety of the slopes and to define the potential slip surface under steady state and rapid drawdown for the selected sections (section A1-A2 and B1-B2) with time. The minimum required factor of safety for the slopes is 1.5 for the steady state condition and 1.0 for rapid drawdown condition. The study showed the values of the safety factor decrease from steady state to rapid drawdown condition. It also showed that the higher the rate of drawdown, the larger the area affected for potential slip surface along the geometry of weaker layer.